Media Laws and Ethics in Selected Muslim Countries - Mohd. Yusof Hussain (2009)
The book contains a collection of essays on the subject â€œMedia Law and Ethics in Selected Muslim Countriesâ€. The countries selected for discussion are Indonesia, Malaysia, Pakistan, and Sudan. Of the eleven chapters, six are on media law, three on media ethics and two discuss both media law and ethics. The discussion revolves around the meaning, purpose, nature, development and measures taken by the government and media organizations to ensure that media practitioners comply with the countryâ€™s media law and ethics.